Acceptability of COVID-19 Certificates: A Qualitative Study in Geneva, Switzerland, in 2020 - Fargnoli, Vanessa; Nehme, Mayssam; Guessous, Idris; Burton-Jeangros, Claudine (Frontiers in Public Health, 2021)
Immunity certificates related to SARS-CoV-2 have been under discussion since the beginning of the pandemic with conflicting opinions. In order to identify arguments in favor and those against the possible implementation of documents certifying one's immunity based on serological testing, we developed a qualitative study in Geneva, Switzerland. The study took place between two lockdowns with a sense of semi-normalcy during summer 2020 in Switzerland but at a time when no vaccine was available and seroprevalence was below 21%. Eleven focus groups with members of the public and fourteen semi-structured interviews with stakeholders were conducted between July and November 2020, with a total of 68 participants with ages between 24 to 77 years old. Interviews and focus groups transcripts were coded with the ATLAS.ti CAQDAS. Few participants considered immunity certificates as an acceptable public health measure. Major concerns included reliability of scientific data related to COVID-19 immunity and serological testing, potential re-infection as well as the possibility that the use of certificates results in deleterious outcomes. Discrimination, counterfeiting, incitement for self-infection, invasion of the private sphere, violation of personal integrity and of medical secrecy were perceived as the major risks. Benefits of immunity certificates were more perceived when in relation to vaccination, included gains in medical knowledge and protection in certain contexts involving leisure or work-related activities. The consequences of implementing immunity certificates are numerous and the acceptability by the general population has to be considered before engaging in such policy. Even if the results provide a snapshot of arguments discussed around immunity certificates based on serological testing before the implementation of COVID-19 vaccine, most of the issues discussed are central in the current debates about vaccine certificates.